2017
DOI: 10.7880/abas.0170916a
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Galapagos Ke-tai’s Dominant Industrial Design

Abstract: The folding "clamshell" mobile phone was chosen as the dominant industrial design in the Japanese mobile phone industry due to the importance of mail functionality, and NEC actively pushed this style and acquired major market share. As a result, at the start of the 21st century, the dominant design "Galapagos ke-tai," unique to Japan, was established. However, this dominant industrial design along with the functionality of these phones became a barrier to the Japanese mobile phone industry when they shifted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…As it is said that having a dominant ID gives a competitive advantage to a firm (Akiike, 2017), the importance of design innovation is being acknowledged. This paper therefore discusses innovation in terms of (1) design innovation and (2) technology innovation.…”
Section: Effects On Innovationmentioning
confidence: 99%
“…As it is said that having a dominant ID gives a competitive advantage to a firm (Akiike, 2017), the importance of design innovation is being acknowledged. This paper therefore discusses innovation in terms of (1) design innovation and (2) technology innovation.…”
Section: Effects On Innovationmentioning
confidence: 99%
“…Therefore, this paper reviewed articles on design thinking. The results showed that (a) while existing review 1 Design management has become popular also in Japan in recent years (e.g., Akiike, 2017;Akiike & Yoshioka-Kobayashi, 2017;Akiike, Yoshioka-Kobayashi, & Katsumata, 2019;Hanahara, 2021). 2 (i), (ii), and (iii) are the authors' classification.…”
Section: Introductionmentioning
confidence: 99%
“…Akiike (2017) explains the diffusion of folding type phones through changes in features.8 According toTakahashi (2015), the iron cage (e.g.,DiMaggio & Powell, 1983 protects corporate management, but at the same time binds it,…”
mentioning
confidence: 99%